Genomic dissection of the cytokine-controlled STAT5 signaling network in liver - Hosui, Atsushi (American Physiological Society, 2008)
Growth hormone (GH) controls the physiology and pathophysiology of the liver, and its signals are conducted by two members of the family of signal transducers and activators of transcription, STAT5A and STAT5B. Mice in which the Stat5a/b locus has been inactivated specifically in hepatocytes display GH resistance, the sex-specific expression of genes associated with liver metabolism and the cytochrome P-450 system is lost, and they develop hepatosteatosis. Several groups have shown by global gene expression profiling that a cadre of STAT5A/B target genes identify genetic cascades induced by GH and other cytokines. Evidence is accumulating that in the absence of STAT5A/B GH aberrantly activates STAT1 and STAT3 and their downstream target genes and thereby offers a partial explanation of some of the physiological alterations observed in Stat5a/b-null mice and human patients. We hypothesize that phenotypic changes observed in the absence of STAT5A/B are due to two distinct molecular consequences: first, the failure of STAT5A/B target genes to be activated by GH and second, the rerouting of GH signaling to other members of the STAT family. Rerouting of GH signaling to STAT1 and STAT3 might partially compensate for the loss of STAT5A/B, but it certainly activates biological programs distinct from STAT5A/B. Here we discuss the extent to which studies on global gene expression profiling have fostered a better understanding of the biology behind cytokine-STAT5A/B networks in hepatocytes. We also explore whether this wealth of information on gene activity can be used to further understand the roles of cytokines in liver disease.